Tinjauan Farmakologi Batang dan Daun Sembung (Blumea balsamifera L.) sebagai Antidiabetes - 10060321017, Tarisa Perolin; Umi Yuniarni; Ratih Aryani (Bandung Conference Series: Pharmacy, 2025)
Abstract. Diabetes melitus (DM) is a degenerative disease associated with disturbances in carbohydrate, fat, and protein metabolism, characterized by hyperglycemia due to decreased insulin secretion and sensitivity, which can lead to various complications. Natural ingredients that have been proven to have antidiabetic activity and can be used as medicinal plants are Blumea balsamifera L. This study aims to examine the pharmacological activity of the stems and leaves of sembung as an antidiabetic. The method used is a systematic review of systematic literature conducted by searching for articles in the last 10 years using the PubMed and Science Direct databases. Then the articles were filtered using Mendeley. There are a total of 5 articles discussing the pharmacological activity of the stems and leaves of sembung as an antidiabetic that meet the inclusion and exclusion criteria. The results of the literature study of the five articles discuss the activity of the stems and sembung with the mechanism of inhibiting the alpha amylase enzyme, the glucosidase enzyme, and reducing blood glucose levels in test animals that have been induced by Streptozocin and Alloxan.Abstrak. Diabetes melitus (DM) merupakan penyakit degeneratif yang disertai gangguan metabolisme karbohidrat, lemak, dan protein, ditandai dengan hiperglikemia akibat menurunnya sekresi dan sensitivitas insulin, yang dapat menimbulkan berbagai komplikasi. Bahan alam yang telah terbukti memiliki aktivitas antidiabetik dan dapat digunakan sebagai tanaman obat adalah Blumea balsamifera L. Penelitian ini bertujuan untuk menelaah aktivitas farmakologi batang dan daun sembung sebagai antidiabetes. Metode yang digunakan yaitu kajian sistematik literatur sistematik yang dilakukan dengan pencarian artikel dalam 10 tahun terakhir menggunakan database PubMed dan Science Direct. Kemudian dilakukan penyaringan artikel menggunakan Mendeley. Terdapat total 5 artikel yang membahas mengenai aktivitas farmakologi batang dan daun sembung sebagai antidiabetes yang memenuhi kriteria inklusi dan ekslusi. Hasil studi literatur dari ke lima artikel membahas mengenai aktivitas batang dan sembung dengan mekanisme penghambatan enzim alfa amilase, enzim glukosidase, dan menurunkan kadar glukosa darah hewan uji yang telah di induksi Streptozocin dan Aloksan.